STRATEGI DINAS KEPENTDUDUKAN DAN PENCATATAN SIPIL DALAM PENINGKATAN PELAYANAN KEPENDUDUKAN DI KOTA TERNATE - Darwis, Fachroji; Lating, Ali; Pora, Rasid (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2024)
Abstract In an increasingly digital-savvy society, greater demands for the speed of public services are a challenge for the government in presenting digital technology-based services to adapt to the times. It is said that digitalisation in public services is not only beneficial for the community, but also for internal public service providers. With optimal service, not only does it give an impact on trust in government performance, but more importantly, the right to other needs will automatically be fulfilled properly. The purpose of this study was to determine the Strategy for Improving Population Administration Services at the Population and Civil Registration Office of Ternate City, The research method used in this research is qualitative research method, the results obtained from observation, interviews and documentation, in this study are primary sources including, Secretary of the Office, Head of Registration and Population Services, Head of Planning Subdivision and Head of Data Utilisation and Information. The results showed that, the improvement of population administration services at the Population and Civil Registration Office of the City was carried out by, among others: First, the digitalisation of services which aims at efficiency both in terms of time and budget and effectiveness in terms of resource utilisation (employees).Second, the ball pick-up strategy where this strategy is carried out by making direct visits from house to house (dor to dor) with two service mechanisms, namely responding to requests directly to service spots and planning well-scheduled programs. However, there are a number of obstacles in the service including limited infrastructure, budget, lack of awareness of the importance of population administration and knowledge related to the use of digital media by the community. It is expected that in the future the Population and Civil Registration Office needs to improve population administration services by preparing adequate infrastructure by allocating sufficient budget, besides that it is important to increase the capacity of employee resources related to the use of digital media in population administration management.